Health expenditures, environmental quality, and economic development: State-of-the-art review and findings in the context of COP26 - Zhenjiang Xing; Xia Liu (Frontiers Media S.A., 2022)
There are numerous factors that affect human health. Among others, environmental degradation, bad governance, and extensive economic growth are regarded as more destructive for health-related issues. To explore the nexus of the said factors and extend the scholarly literature, the current study aims to analyze the influence of greenhouse gas (GHG) emissions, governance indicators, and gross domestic product (GDP) on human health expenditures-captured by domestic health expenditures and capital health expenditures. Specifically, this study contrasted variables including regulatory quality (RQ), rule of law (RL), GDP, GHG emissions, and human capital (HC) with that of human health expenditure. Covering the period from 1996 to 2020, this study uses time series specifications in the case of China, which is one of the largest pollution-emitting economies across the globe. The empirical results found that the long-run equilibrium relationship exists between the variables. For the long-run coefficients, this study utilizes the fully modified ordinary least square, dynamic ordinary least square, and canonical cointegration regression, suggesting that economic development and RQ are adversely affecting human health expenditure. However, GHG emissions, RQ, and HC significantly improve human health by increasing health expenditure in China. Based on the empirical results, policies are suggested regarding human health improvement, improved governance quality, and environmental sustainability. The study discusses the empirical conclusions and implications as per COP26 declarations.